Conventional Corneal Collagen Cross-Linking Versus Transepithelial Diluted Alcohol and Iontophoresis-Assisted Corneal Cross-Linking in Progressive Keratoconus. Issue 12 (December 2017) - Bilgihan, Kamil; Yesilirmak, Nilufer; Altay, Yesim; Yuvarlak, Armagan; Ozdemir, Huseyin Baran
Abstract : Purpose: To compare clinical outcomes of conventional corneal cross-linking (C-CXL) and diluted alcohol and iontophoresis-assisted corneal cross-linking (DAI-CXL) for the treatment of progressive keratoconus (KC). Methods: Ninety-three eyes of 80 patients with KC were treated by C-CXL (n = 47) or DAI-CXL (n = 46). Visual acuity, keratometry, KC indexes, pachymetry, and aberrations were recorded before treatment and 1, 3, 6, and 12 months after treatment. The demarcation line was assessed 1 month after treatment. Results: A significant improvement in visual acuity was observed at month 3 and month 6 after DAI-CXL and C-CXL, respectively. A significant decrease in maximum keratometry was observed in both groups at month 6. The front symmetry index significantly improved in both groups after 6 months, whereas the Baiocchi Calossi Versaci index significantly improved only after DAI-CXL at month 12 ( P = 0.01). Average keratometry and other KC indexes were stable during 12 months of follow-up. Central corneal thickness decreased by 28.6 and 40.2 μm after DAI-CXL and C-CXL at month 1, respectively ( P < 0.01), and it reached baseline at the 12th month ( P = 0.14) only in the DAI-CXL group. Higher-order aberrations, coma, and spherical aberration significantly worsened at month 1 ( P < 0.01) only after C-CXL; however, they improved significantly at month 12 compared with baseline ( P < 0.05) in both groups. The demarcation line was visible in all cases at month 1 at a mean depth of 302 ± 56 μm and 311 ± 57 μm after DAI-CXL and C-CXL, respectively ( P = 0.7). Conclusions: The DAI-CXL protocol seems as effective as the C-CXL protocol in halting KC progression after 1 year of follow-up. Abstract : Supplemental Digital Content is Available in the Text.